2012
DOI: 10.1093/scan/nsr078
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and hippocampus fail to habituate to faces in individuals with an inhibited temperament

Abstract: Habituation is a basic form of learning that reflects the adaptive reduction in responses to a stimulus that is neither threatening nor rewarding. Extremely shy, or inhibited individuals, are typically slow to acclimate to new people, a behavioral pattern that may reflect slower habituation to novelty. To test this hypothesis, we used functional magnetic resonance imaging to examine habituation to neutral faces in 39 young adults with either an extreme inhibited or extreme uninhibited temperament. Our investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 46 publications
10
95
1
Order By: Relevance
“…We calculated two different amygdala habituation indices: (1) the amplitude difference between the first and last stimulation block (FmL; Blackford et al, 2013) and (2) modeling of habituation by means of the regression (REG) approach.…”
Section: Habituation Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated two different amygdala habituation indices: (1) the amplitude difference between the first and last stimulation block (FmL; Blackford et al, 2013) and (2) modeling of habituation by means of the regression (REG) approach.…”
Section: Habituation Analysesmentioning
confidence: 99%
“…Several studies have also demonstrated hemispheric lateralization with stronger habituation in the right versus left amygdala (Denny et al, in press;Lonsdorf et al, 2011;Phillips et al, 2001;Wedig et al, 2005;Wright et al, 2001). Of particular interest from the clinical perspective, amygdala habituation has been shown to be negatively correlated with trait anxiety (Hare et al, 2008), increased risk for social anxiety disorder (Blackford et al, 2013) and autism spectrum disorder (Kleinhans et al, 2009;Swartz et al, 2013;Wiggins et al,2014). Furthermore, it is sensitive to genetic variants linked to depression, anxiety, aggression and neuroticism (Fisher et al, 2009;Lonsdorf et al, 2011;Wiggins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…fMRI studies employing "less threatening" social stimuli have demonstrated increased modulation of the dorsal (dACC) and superior temporal sulcus to faces with moderate emotional intensity and ambiguous faces, respectively, in shy adults (Tatham, Schmidt, Beaton, Schulkin, & Hall, 2013); and sustained amygdalar and hippocampal activation to neutral faces in a 2 TANG ET AL. group of extremely inhibited individuals, although some of them met criteria for social anxiety disorders (Blackford, Allen, Cowan, & Avery, 2013). Greater modulation of brain regions involved in attention, planning, and higher order visual processing have also been observed in individuals scoring high on sensory processing sensitivity (SPS) in response to both positive and negative facial expressions (Acevedo et al, 2014) and to subtle discrepancies in non-social scenic stimuli (Jagiellowicz et al, 2010).…”
Section: Shyness and Sensitivity To Threatmentioning
confidence: 99%
“…Previous research indicates the hippocampus may be involved in risk for anxiety in terms of structure [48], function [49], and behavior [19]. Reduced hippocampal activity in the high AMBI group could enhance learning in standard delay (500-ms) conditioning.…”
Section: Discussionmentioning
confidence: 93%